Translation of the Imperative Forms in the Holy Qur'an - Elaissawi, Ibrahim El Sayed (2016)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Ibrahim El Sayed Elaissawi entitled, "Translation of the Imperative Forms in the Holy Qur'an," submitted in May 2016. Thesis advisor is Dr. Ahmed Ali. Soft and hard copy available.